The 2-arsaethynolate anion. Synthesis and reactivity towards heteroallenes - Hinz, A; Goicoechea, J (Wiley, 2016)
We report the synthesis and isolation of the 2-arsaethynolate anion and its subsequent reactivity towards heteroallenes. Reactions with ketenes and carbodiimides afford four-membered anionic heterocycles in formal [2+2] cycloaddition reactions. By contrast, reaction with an isocyanate yielded a 1,4-diaza-2-arsoidine-3,5-dionide anion and the unprecedented cluster anions As102– and As124–. These preliminary reactivity studies hint at the enormous potential synthetic utility of this novel anion, which may be employed as an arsenide (As–) source.